The Latest in Peritoneal Dialysis - Aguilera Peralta, Abelardo (IntechOpen, 2013)
This book summarizes the advances and new concepts introduced in the last years on peritoneal dialysis (PD) and its complications. PD therapy is a renal replacement peritoneal membrane using a semi-permeable barrier to liquids and solutes. The abdominal cavity with all its components, mesothelial cells, fat tissue, immune system components and others are activated by the PD fluids that although every time are more biocompatible, induce production of molecules with the local and systemic effects. Locally there is a thickening of the peritoneal membrane leading to the failure of this and where the transdifferentiation of mesothelial cells plays a key role. Systemically activating abdominal cavity appears to be involved in atherosclerosis, diabetes, hypertension, renal bone disease pathway and others.